PRODUKSI SUSU SAPI PERAH FRIESIAN HOLSTEIN (FH) PADA PERIODE LAKTASI YANG BERBEDA (Milk Production of Friesian Holstein (FH) Cows at Different Lactation Periods) - Ali Mahmud; Woro Busono; Puguh Surjowardojo; Yuli Arif Tribudi (Jurnal Ilmu dan Teknologi Peternakan, 2020)
This research was conducted in PT Greenfields Indonesia, Babadan Village, Ngajum Districts, Malang, East Java. The purpose of the study was to compare the milk production of FH (Friesian Holstein) dairy cows in various lactation periods. The material used in this research was data records of Australian FH, which have been developed in the Greenfields Indonesia farm. The data used were from 473 dairy cows, which consisted of 100 heads for each lactation period from the period I up to period IV and 73 heads for lactation period V. The variables measured were milk production 305 day 2X ME, daily milk yield production, peak day production, and the peak lactation. The data were analyzed using analysis of variance, and if the result showed differences, the analysis was continued using the Duncan test. The results showed that the increase in the lactation period significantly (P<0.01) decreased milk production and increased the duration of lactation peaks of FH cows. The highest milk production 305 day 2X ME was in the lactation period II, which was around 10232.90 ± 1036.62 kg/lactation or 32 ± 5.13 kg/day. In this period, the peak day in milk lactation was 71.5 ± 27.5 days, and the peak of milk production was 45.7 ± 4.1 kg/day. In conclusion, milk production increased from the first lactation period to the second lactation period and then decreased in subsequent periods. The peak of the first lactation period was reached longer, then falls in the second lactation period and then increases again at the following lactation period